2023
DOI: 10.1093/plphys/kiad065
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenase MnGutB1 catalyzes 1-deoxynojirimycin biosynthesis in mulberry

Abstract: As the prevalence of diabetes continues to increase, the number of individuals living with diabetes complications will reach an unprecedented magnitude. Continuous use of some synthetic agents to reduce blood glucose levels causes severe side effects, and thus, the demand for non-toxic, affordable drugs persists. Naturally occurring compounds, such as iminosugars derived from the mulberry (Morus spp.), have been shown to reduce blood glucose levels. In mulberry, 1-deoxynojirimycin (DNJ) is the predominant imin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…BRs regulate plant cell elongation and division, light sensing, vascular differentiation, flowering, male reproduction, and stress resistance (Clouse, 2011;Fabregas et al, 2018;Gupta et al, 2020). Moreover, BR regulates organ boundary determination, stomatal differentiation, root meristem maintenance, immune response, root hair formation, shoot branching, and leaf angle control in monocots (Shang et al, 2016;Nolan et al, 2017;Xia et al, 2021;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…BRs regulate plant cell elongation and division, light sensing, vascular differentiation, flowering, male reproduction, and stress resistance (Clouse, 2011;Fabregas et al, 2018;Gupta et al, 2020). Moreover, BR regulates organ boundary determination, stomatal differentiation, root meristem maintenance, immune response, root hair formation, shoot branching, and leaf angle control in monocots (Shang et al, 2016;Nolan et al, 2017;Xia et al, 2021;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, Yang et al (2023) identified an amino-polyol dehydrogenase in mulberry that participates in the biosynthesis of antihyperglycemia azasugar DNJ. They provided evidence for its biochemical activity, presented data on tissue localization of DNJ biosynthesis, and supplied an explanation for the photoperiodical dependency of DNJ contents in mulberry.…”
mentioning
confidence: 95%
“…In this issue of Plant Physiology , Yang et al (2023) provide clear evidence that a 2-amino-2-deoxy-D-mannitol (ADM) dehydrogenase, MnGUTB1, participates in the biosynthesis of the azasugar DNJ, catalyzing the oxidation of ADM to NJ in mulberry ( Fig. 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations